Corporate Social Responsibility: Organizational Strategy for Sustainable Growth - Park, Byung Il; Xiao, Simon Shufeng (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
We often cast a question whether unethical behavior (corporate irresponsible activities) undertaken by international firms in developing countries is really entirely unethical or simply unavoidable grease, which is necessary to facilitate short-term growth in overseas markets. Both strategic management and international business scholars have long attempted to examine the outcomes of corporate social responsibility (CSR) primarily in the organizational strategic aspect. Due to this, they are turning a blind eye to firms' unethical attitude and pretending not to notice that it is happening. In other words, we do not yet know enough about CSR from a long-term perspective and its relationship with sustainable growth for the long-term. We should also acknowledge that a firm's unethical management is both a primary cause and a result of poverty in our economy, which means that a firm's irresponsible activities (as an antonym of CSR) cannot be justified by any reason. This also represents the importance of research exploring CSR. We believe that this is the time to, first, synthesize diverse research fragments on CSR, second, combine it with an additional unique agenda (e.g., human rights, win-win partnership, official development assistance) particularly in the sustainability domain, and then third, compile all the theoretical and empirical pieces for organizational sustainability. By inviting submissions from researchers who studies various theoretical perspectives, adopts varied empirical approaches, and examines at multiple levels of analysis, as well as qualitative and quantitative experiments, literature reviews, and meta-analyses, this SI draws a big picture. We are strongly convinced that papers accepted by this SI significantly contribute to current relevant debates by filling many extant research gaps.